PENGARUH BIMBINGAN KELOMPOK TEKNIK ROLE PLAYING DALAM MENGELOLA EMOSI DIRI SISWA SMA DENGAN PENDEKATAN PENDIDIKAN ISLAM - Anggraini, Siska Ardilla; Ali Daud Hasibuan; Ira Suryani (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2024)
The study entitled "The Effect of Group Guidance Role Playing Techniques in Managing High School Students' Self-Emotions with an Islamic Education Approach" aims to overcome the problem of managing students' emotions that often trigger disputes, difficulties in expressing emotions, and excessive joking behavior. This study used a quantitative approach with a One Group Pretest-Posttest design and involved 10 grade X students at SMA Budi Agung Medan who were selected through purposive sampling. Data were collected using emotion management scale and analyzed by Wilcoxon test. The results showed that the role playing technique significantly improved students' ability to manage emotions, with a value of Zhitung = -2.803 and p = 0.005 < 0.05. These findings indicate the importance of implementing group guidance services with specific techniques in schools to develop students' potential.